Evacuation Route Planning at Batu Dam, Selangor - Syed Hashim, Syarifah Intan Najla; Abu Talib, Siti Hidayah; Abustan, Muhammad Salleh (International Journal of Sustainable Construction Engineering and Technology, 2026)
This research analyzes evacuation planning around the Batu Dam in Malaysia, focusing on the risks from dam overtopping due to heavy rainfall and climate change. It emphasizes understanding population density in the Gombak District using a city population web application for effective disaster risk management and urban planning. The study details specific evacuation routes, distances, travel times, flood arrival estimates, and populations served in the Batu Caves area, which are crucial for ensuring safe resident movement to designated safe zones during emergencies. Factors such as proximity to urban areas, economic opportunities and land use influence population density, making it a key consideration in developing these plans. The research categorizes population density based on Malaysian statistics, highlighting its importance in identifying high-risk areas and ensuring resident safety and well-being.